The application of fNIRS in studies on occupational workload: a systematic review - Gemmerich, Robin; Müller, Ole; Schaller, Andrea (Frontiers in Public Health, 2025)
BackgroundOccupational workload can contribute to significant health problems such as chronic stress, fatigue and burnout. To investigate the underlying mechanisms, it is necessary to monitor brain activity in real work environments. Functional near-infrared spectroscopy (fNIRS) is a portable, non-invasive neuroimaging method that captures neural correlates of occupational workload under natural conditions. However, despite its increasing application, a comprehensive overview of fNIRS-based research in this field is lacking. Therefore, this systematic review examines how fNIRS can be utilized to investigate occupational workload.MethodsFollowing PRISMA 2020 guidelines, we conducted our systematic review by searching Web of Science, PubMed, and Scopus between November 15, 2023 and March 20, 2025. We included all studies published in English or German at any date, as long as they examined healthy adult professionals performing occupational tasks with functional near-infrared spectroscopy (fNIRS). Extracted data included study characteristics, workload details, signal processing methods, main fNIRS findings, and study quality, assessed using the JBI Critical Appraisal Tool.ResultsWe included 41 studies. Of these, 23 reported a significant increase in oxygenated hemoglobin (HbO) concentration and functional connectivity in the prefrontal cortex (PFC) under higher occupational workload conditions. Only five studies examined typical office tasks. Nine studies analyzed differences in cortical activation between experts and novices, with experts showing increased HbO concentration in the PFC than novices. Regarding methodology, 26 studies used standardized optode placements, while only 17 applied systemic and extracerebral artifact correction. Small sample sizes and the absence of randomized controlled trials limited the reliability and reproducibility of the findings.ConclusionFunctional near-infrared spectroscopy effectively detects neural correlates of occupational workload and provides objective insights into cognitive demands in real-world work settings. Standardizing optode placement, harmonizing signal-processing methods, and increasing sample sizes would enhance the validity and comparability of future research. Expanding investigations to typical office environments is also crucial for understanding daily workload and for developing interventions that promote employee well-being and productivity. Overall, fNIRS represents a promising tool for establishing evidence-based workplace health promotion strategies across diverse occupational settings.